Design and Fabrication of a Mobile Water Supply System For Drip Irrigation. - Lutwetwe Shadrack (Kabale University, 2023)
In this study, a design and fabrication of a mobile water supply system for drip irrigation was undertaken thus the major aim of this project is to eliminate the existing out fashioned drip irrigation methods such as the use of water bottles and stationary water supply system for drip irrigation to improve on the Agricultural yield from the crops. A survey was undertaken to establish the day-to-day methods stil1 in existence for drip irrigation, thus this was to give an overview of the need to have a cheaper design that is simple and cost-effective. This involved collection of resources from different sources to obtain important data for the project and having a guideline on the steps involved in the design. The specific objectives will entail the determination of pertinent parameters for the conceptual design and coming up with the system layout generated from 3D modeling software (DS SOLID WORKS), selecting material, sizing the components that are necessary for the machine, and fabricating the prototype. Thus, the design and fabrication of a mobile water supply system for drip irrigation will be done, stating design specifications, developing conceptual designs, sizing of the solar components, and details of the design of the selected concept with its working drawings. Therefore, various sources of the data (references) given in this report are also provided at the end of the document.